Determination of Aflatoxin M1 in Raw Milk: A Review of an Island Sample with the HPLC Method - Tuncay, Cangul; Oniz, Adile (Progress in Nutrition, 2022)
This study has been conducted to determine the frequency of aflatoxin M1 (AFM1) contamination in raw milk produced across six zones of Cyprus between 2018-2020 in accordance with seasonality and production regions. A total of 1,026 samples of raw milk were collected from the different production regions of the 6 provinces between September 2018 and August 2020. AFM1 analyses were conducted using the HPLC method. On average, AFM1 contamination of the total of 1,026 raw milk samples was determined to be 26.4±17.96 ng/L. It was found that only 11.4% of the raw milk samples exceeded the legal limit of the European Union (50 ng/L). AFM1 contamination incidence in raw milk samples is much higher in autumn and winter (average 31.77±19.21 ng/L and 26.96±20.77 ng/L, respectively) compared to spring and summer (average 19.00±18.53 ng/L and 7.51±11.31 ng/L, respectively). For this reason, it is important to monitor AFM1 contamination in raw milk in autumn and winter. This comprehensive study, which is the first of its kind in Cyprus, will promote the management and future risk analysis of AFM1 contamination in raw milk across the region.